Obtaining parental consent--opting in or opting out? - Mutch, L (1985)
In a population based project aimed at identifying children with specified disabilities within a health region, there was, rightly, concern about the transfer of data on named children across health district boundaries. Two methods of obtaining parental consent for this process were tested. High recruitment rates were achieved using an 'opting out' approach.